1996
DOI: 10.1002/hep.510240412
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Galactose Elimination Capacity in Patients With Alcoholic Cirrhosis: Possible Use As A Surrogate Marker for Death

Abstract: There is increasing interest for the use of surrogate end points in the evaluation of treatments in patients with liver disease, but adequate validation is seldom available. This study aimed to describe the different course of galactose elimination capacity in patients with alcoholic cirrhosis who continued to drink or abstained from alcohol consumption during follow-up, and to validate changes in galactose elimination as a surrogate end point for death from liver-related causes. Forty-five patients with alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Our findings are consistent with the existing studies of GEC and mortality of cirrhosis patients [6-12,26,27], but our study extends them by being sufficiently large to examine subgroups; by examining both cirrhosis-related mortality and mortality from other causes; by having complete long-term follow-up; by presenting a near-continuous relationship between GEC and short- and long-term mortality; and by adjusting for relevant confounders.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with the existing studies of GEC and mortality of cirrhosis patients [6-12,26,27], but our study extends them by being sufficiently large to examine subgroups; by examining both cirrhosis-related mortality and mortality from other causes; by having complete long-term follow-up; by presenting a near-continuous relationship between GEC and short- and long-term mortality; and by adjusting for relevant confounders.…”
Section: Discussionsupporting
confidence: 91%
“…7,8 Abstinence is also effective in the more severe stages of ALD, and increases survival even in decompensated cirrhotics. 3,9 However, the high rate of recidivism in alcoholics prevents abstinence from being generally effective for ALD. Liver transplantation is also an effective means to treat ALD; however, issues such as organ shortage and costs limit this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…When corrected for the amount of galactose excreted in urine, an approximate estimate of the hepatic V max for galactose is achieved from the blood disappearance curve using blood concentrations ensuring near-saturation of the enzymatic system [1–4]. The GEC accurately assessed survival prognosis of patients with acute liver failure [5], chronic liver disease [6,7], and patients undergoing liver resection [8]. More interestingly, it has been shown that quantitative liver function tests such as the GEC are far more predictive of the remaining liver function following partial hepatectomy than measurements of liver volumes [911].…”
Section: Introductionmentioning
confidence: 99%